Regulating Fake News and Hoaxes: A Comparative Analysis of Indonesia and Malaysia - Supanto, Supanto; Saefudin, Yusuf; Ismail, Noorfajri; Susanti, Rahtami; Adi, Lutfhi Kalbu (Lembaga Contrarius Indonesia, 2023)
Indonesia and Malaysia already have regulations prohibiting the spreading of fake news and hoaxes. However, the critical question is whether these regulations can tackle the spread of fake news and hoaxes, considering their detrimental impact on the economy and reputation. This is aimed at comprehensively understanding the legal framework in both countries. This research was designed using the normative juridical method. The approaches used are statutory approach, conceptual approach, and comparative approach. The result show Indonesia's penal policy was recently created by passing a new Criminal Code. It seeks to protect public order, public welfare, and democratic values, emphasizing a balance between freedom of speech and combating the adverse effects of hoax and fake news. Meanwhile, Malaysia employs regulatory measures through the Communication and Multimedia Content Forum, relying on voluntary compliance and cooperation from various stakeholders. Looking ahead, emerging technologies and methodologies in digital forensics offer promise for more effective means of identifying the origins of fake news